PENGARUH TINGKAT PERTUMBUHAN PENJUALAN DAN PERPUTARAN PIUTANG TERHADAP LIKUIDITAS PADA PT. PERKEBUNAN NUSANTARA VIII PERIODE 2011-2020 - Syifa Vidya Sofwan; Aditya Achmad Fathony; Yulia Rachmawati (Fakultas Ekonomi UNIBBA, 2022)
This study analyzes the Effect of Sales Growth Rate and Accounts Receivable Turnover on Liquidity at PT. Perkebunan Nusantara VIII. The method used in this research is descriptive analysis method with a quantitative approach. Based on the results of hypothesis testing, that simultaneously the Sales Growth Rate and Accounts Receivable Turnover have a significant effect on Liquidity with the result of the Coefficient of Determination of 89.9% and the remaining 11.1% are other variables that also affect Liquidity but are not examined. As for the partial sales growth rate does not have a significant effect on liquidity, this is evidenced by the results of the t test where tcount is smaller than ttable. Then Accounts Receivable Turnover partially has a significant effect on Liquidity, this is evidenced by the results of the t test where tcount is greater than ttable